2014
DOI: 10.3390/children1020241
|View full text |Cite
|
Sign up to set email alerts
|

Turning the World Upside Down: Playing as the Deliberate Creation of Uncertainty

Abstract: Risk is big business. It has assumed almost universal acceptance as an ever-present reality of life, something out there waiting to cause harm (most notably to political, economic and health systems). It commands vast resources to develop preventative measures that are the preserve of experts issuing often contradictory advice and warnings. Children’s play is caught up in this account. No longer something that children just do, it is subject to adult scrutiny that simultaneously and paradoxically attempts to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 72 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…Limiting this diverse and complex behavior to a specific instrumental purpose can marginalize diverse forms of play that are not active, and reshape children's conceptions of play as purposeless-a defining characteristic of play [19,21]. Recent research indicated that this instrumental notion of play has influenced children's descriptions of play.…”
Section: Introductionmentioning
confidence: 94%
“…Limiting this diverse and complex behavior to a specific instrumental purpose can marginalize diverse forms of play that are not active, and reshape children's conceptions of play as purposeless-a defining characteristic of play [19,21]. Recent research indicated that this instrumental notion of play has influenced children's descriptions of play.…”
Section: Introductionmentioning
confidence: 94%
“…We didn't tell any one". Children navigated situations of uncertainty (Lester, 2014), engaging with ethi cal decisionmaking and making existential connections to each other and the world around them.…”
Section: Making Breaking and Following The Rulesmentioning
confidence: 99%
“…Certainly, it should be recognised that a key charge that may be levelled at attempts to translate new materialism into empirical research is that they risk somewhat endlessly describing manifold ways in which nonhumans 'act'. In one sense, this move might be welcomed: as with studies of children's play, there is a certain politics, ethics and aesthetics to recognising the intrinsic significance of different forms of nonhuman agency (Lester and Russell, 2014). In another sense, however, one might ask what should happen next?…”
Section: A Double-bind? Taking New Materialisms Elsewhere In Studies mentioning
confidence: 99%